1980
DOI: 10.1115/1.3224796
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Side-Grooves in Estimating JIc Fracture Toughness With Charpy-Size Specimens

Abstract: The problem of obtaining a meaningful value of toughness from small Charpy-size surveillance specimens, tested at temperature corresponding to the upper shelf where ductile fracture predominates, is investigated. Following the procedures of Green and Knott for measurement of crack opening displacements at initiation of ductile fracture, a test procedure is adopted in which small precracked Charpy-size bend specimens are side-grooved to increasing depths and tested to failure under both quasi-static and dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

1982
1982
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…In general, the tilt,, ratios were greater than 0.50. This is in conformity with the reported suggestion that with precracking and/or side-grooving and/or using embrittled specimens, the point of crack initiation approaches the point of maximum load [40,45]. The Ej/ET ratio (where ET is the total impact energy) was mostly 20% or higher in the present case.…”
Section: Estimates Of N M D and Gydsupporting
confidence: 94%
“…In general, the tilt,, ratios were greater than 0.50. This is in conformity with the reported suggestion that with precracking and/or side-grooving and/or using embrittled specimens, the point of crack initiation approaches the point of maximum load [40,45]. The Ej/ET ratio (where ET is the total impact energy) was mostly 20% or higher in the present case.…”
Section: Estimates Of N M D and Gydsupporting
confidence: 94%
“…Prior investigations [I [13][14][15][16] have indicated that side-grooves can promote plane strain fractirre in thin sections which usually exhibit ductile behavior. Other studies show that side-grooves may also affect fatigue crack growth by lowering closure loads [ 171 and slightly decreasing thick specimen retardation [18].…”
Section: Introductionmentioning
confidence: 99%
“…5). Bei seitengekerbten Proben ist es mo Èglich, aus der Maximalkraft einen angena Èherten Wert fu Èr die Risseinleitungsza Èhigkeit zu bestimmen [53].…”
Section: Der Konventionelle Kerbschlagbiegeversuchunclassified